How Satisfaction Research Contributes to the Optimization of Urban Green Space Design—A Global Perspective Bibliometric Analysis from 2001 to 2024 - Shaoying Zhang; Mastura Adam; Norafida Ab Ghafar (Land)
With rapid global sustainable growth and urbanization, green spaces—central to urban green infrastructure—provide essential ecosystem services that significantly enhance residents’ quality of life and well-being. This importance has grown even more evident during the COVID-19 pandemic. Therefore, the research on satisfaction with urban green spaces has become an essential topic for scholars in recent years. A systematic review could be helpful as research trends and effective optimization strategies are still unclear. To fill this gap, this study conducted a bibliometric analysis of 313 high-quality papers published on the Web of Science since 2001. The findings revealed: (1) Key journals and significant developments associated with this field of research, especially from China and the United States, emerging as the major contributors. (2) Keyword clustering analysis identified key themes, including public engagement, historic preservation, environmental justice, walkability, green space accessibility, and restorative environments. These findings emphasize the importance of data-driven and innovative planning strategies for enhancing residents’ well-being, tourism, and urban sustainability. (3) Research on satisfaction with urban green spaces has shifted from a singular to a more diversified focus, contributing to the optimization of urban green spaces through four main aspects: residents’ needs, ecological functions, management strategies, and research approaches. The conclusions offer strategies for researching the optimization of urban green spaces and provide valuable insights for residents, scholars, urban planners, and designers.